Uncemented femoral stems for revision surgery : the press-fit concept - planning - surgical technique - evaluation /: the press-fit concept - planning - surgical technique - evaluation. (2015) - Le Béguec, Pierre; Canovas, François; Roche, Olivier; Goldschild, Mathias; Batard, Julien
No abstract available